Ammonium Inhibits Chromomethylase 3-Mediated Methylation of the Arabidopsis Nitrate Reductase Gene NIA2 - Kim, Joo Yong; Kwon, Ye Jin; Kim, Sung-Il; Kim, Do Youn; Song, Jong Tae; Seo, Hak Soo (Frontiers in Plant Science, 2016)
Gene methylation is an important mechanism regulating gene expression and genome stability. Our previous work showed that methylation of the nitrate reductase (NR) gene NIA2 was dependent on chromomethylase 3 (CMT3). Here, we show that CMT3-mediated NIA2 methylation is regulated by ammonium in Arabidopsis thaliana. CHG sequences (where H can be A, T, or C) were methylated in NIA2 but not in NIA1, and ammonium [(NH4)2SO4] treatment completely blocked CHG methylation in NIA2. By contrast, ammonium had no effect on CMT3 methylation, indicating that ammonium negatively regulates CMT3-mediated NIA2 methylation without affecting CMT3 methylation. Ammonium upregulated NIA2 mRNA expression, which was consistent with the repression of NIA2 methylation by ammonium. Ammonium treatment also reduced the overall genome methylation level of wild-type Arabidopsis. Moreover, CMT3 bound to specific promoter and intragenic regions of NIA2. These combined results indicate that ammonium inhibits CMT3-mediated methylation of NIA2 and that of other target genes, and CMT3 selectively binds to target DNA sequences for methylation.